Homeownership in Low-Income Communities in Indonesia: The Role of Poverty Levels, Inflation, and Bank Indonesia Rate - Hafidzi, Achmad Hasan; Afroh, Ibna Kamilia Fiel (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
Rapid population growth is an important problem for developing countries like Indonesia. The large population must be managed appropriately to minimize inequality that occurs in society, one of which is where they live. A house is one of the most needed fixed assets in the lives of Indonesian people. Homeownership that reaches all elements of society can reduce the poverty gap. Poverty is the main factor for people in owning a house. Apart from that, there are inflation and BI rate factors that influence people's ability to own a house. Inflation is a trigger for the purchasing power of low-income people to own a place to live. The BI rate is an important factor in determining mortgage interest rates so it has an impact on the purchasing power of low-income people. The higher the BI Rate is inversely proportional to people's ability to own a private residence. It is hoped that the fixed interest rate regulated by the government will be able to meet people's needs in buying houses and increase the purchasing power of low-income people.